PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA PEGAWAI - Neli Yurnalis (Manajer Pendididikan, 2019)
This qualitative study aimed at describing the role of headmaster in improving performance accounting staf in SMA Negeri 1 Kepahiang. The results of this study stated that role consist: First role of headmaster as administrator and leader have been put accross to utilize to support to make of accounting staff performance. Peculiarly can be concluded that is role of headmaster as leader done by various policy that is: using network system/LAN in management of administration, library base on Technology Informatika. Second role of headmaster as administrator done by arranging study administration, office administration and pupil, Officer administration, supply administration, financial administration and relation administration go to school with society. Third supplementary factor is available of adequate facility in solving of school administration, amount of accounting staff answer the demand for the management accounting of school, and basic facilities go to school very is supporting. Management study process and administration. Fourth factor Resistor is skill of accounting staff in management administration go to school not yet is adequate and the quality of human resource which still lower, education the accounting as according to profession not yet.